Professionalism and the poetic persona in archaic Greece - Stewart, Edmund (Cambridge University Press, 2016)
Greek poets of the archaic period, though often characterised as amateur aristocrats, could also seek to present themselves as professionals – regular practitioners of a specialist skill (τέχνη). In this capacity, the poet is understood to work primarily for the benefit of the community (either his own or, more commonly, those through which he travels). In return for these services, he expects to receive both a special status and material rewards (though financial gain is not presented as his main motivation). The poet’s professional status thus forms one part of his identity and is a source of respect in the ancient city.